Parvovirus B19-associated eruptive pseudoangiomatosis in a child: The paradigm of paraviral eruptions - Nikkels, Arjen F.; Blaise, Géraldine; Piérard, Gérald E. (Journal of Pediatric Infectious Diseases, 2007)
A 12-year-old otherwise healthy boy developed eruptive pseudoangiomatosis (EPA) of the upper limbs. Meanwhile parvovirus B19 seroconversion became evident. Histology revealed ectasia of blood vessels in the superficial dermis without noteworthy inflammatory cell infiltration. No parvovirus B19 antigens were demonstrated by immunohistochemistry in the endothelial cells, suggesting that this case report of EPA represented a possible paraviral eruption. To the best of our knowledge, this case study is the first to relate primary parvovirus B19 infection and EPA. We suggest that parvovirus B19 could be added to the list of viral agents associated with EPA.
Keywords: Parvovirus B19; eruption; pseudoangiomatosis